2012
DOI: 10.1146/annurev-cellbio-101011-155705
|View full text |Cite
|
Sign up to set email alerts
|

Second Messenger Regulation of Biofilm Formation: Breakthroughs in Understanding c-di-GMP Effector Systems

Abstract: The second messenger bis-(3′-5′)-cyclic dimeric guanosine monophosphate (c-di-GMP) has emerged as a broadly conserved intracellular signaling molecule. This soluble molecule is important for controlling biofilm formation, adhesion, motility, virulence, and cell morphogenesis in diverse bacterial species. But how is the typical bacterial cell able to coordinate the actions of upward of 50 proteins involved in synthesizing, degrading, and binding c-di-GMP? Understanding the specificity of c-di-GMP signaling in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
165
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(189 citation statements)
references
References 117 publications
(245 reference statements)
2
165
0
11
Order By: Relevance
“…Thus, we found a novel mechanism of control of bacterial c-di-AMP synthesis via RadA-DisA interaction in M. smegmatis. In recent years, accumulating evidence has shown that cyclic dinucleotides widely function as second messengers that control multiple microbial phenotypes and physiological characteristics (4,5,(25)(26)(27)(28). Compared with the clearly characterized functions for c-di-GMP in many bacteria (4,5,28), much less is known about the control of c-di-AMP synthesis and its effects on bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we found a novel mechanism of control of bacterial c-di-AMP synthesis via RadA-DisA interaction in M. smegmatis. In recent years, accumulating evidence has shown that cyclic dinucleotides widely function as second messengers that control multiple microbial phenotypes and physiological characteristics (4,5,(25)(26)(27)(28). Compared with the clearly characterized functions for c-di-GMP in many bacteria (4,5,28), much less is known about the control of c-di-AMP synthesis and its effects on bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…The cAMP signaling pathway also interacts with the c-di-GMP pathway, playing a role in regulating V. cholerae biofilm formation (472). The c-di-GMP signaling mechanism represents a unifying principle governing the microbial switch from a planktonic to a sessile lifestyle (514,515). …”
Section: Centralized Regulation By Second Messengersmentioning
confidence: 99%
“…transcription factor | σ 54 | AAA+ protein | competitive inhibition B is-(3′-5′)-cyclic diguanosine monophosphate (c-di-GMP) is an ubiquitous second messenger in bacteria, where it affects the transition between a motile planktonic lifestyle and an adhesive biofilm lifestyle by binding to various effector proteins to modulate enzymatic activity, protein-protein interactions, transcription, and translation (1)(2)(3)(4)(5)(6). One of these effector proteins is FleQ (PA1097), an enhancer-binding protein (EBP) transcription factor from the opportunistic pathogen Pseudomonas aeruginosa.…”
mentioning
confidence: 99%